Tuning the torsional stiffness of aluminum ski laminates using soft materials and cut patterns - Berthon, L.; Audet, J.; Gosselin, P.; Lussier-Desbiens, A. (Sports Engineering, 2025)
Recently, the sports industry has been actively developing products to reduce their environmental impacts. Life Cycle Assessments of alpine skis have unveiled that petroleum-sourced materials, such as resin (phenolic, epoxy, etc.), and fibre reinforcements (carbon, fibreglass), contribute substantially to environmental degradation. To address this, some manufacturers have introduced alternative reinforcement like flax fibre, basalt fibre, or aluminum that can lower a ski`s carbon footprint from production to disposal. While aluminum reinforcements can allow for more of a ski to be recyclable, they also typically increase its torsional stiffness of the skis. This paper explores strategies to reduce the torsional stiffness associated with aluminum-containing ski-like laminates, seeking to achieve comparable levels to traditional composite laminates. To do so, the proposed strategies are validated on ski-like laminate coupons and implemented in ski prototypes. By incorporating soft materials between the wood core and the reinforcement layers, an overall reduction in torsional stiffness up to 40% was reached, close to the variation observed in commercial products (46%). Similar results are attained by introducing longitudinal cut patterns in aluminum sheets. Importantly, these two strategies exhibit limited impact on bending stiffness, and can be used together to reduce the torsional stiffness by 77%.